(untitled) (SCIENCE TIME JOURNAL, 2026)
This article provides a comprehensive analysis of the role of time management techniques in improving performance in the IELTS Reading module among EFL learners. It explores both theoretical and practical dimensions of reading under time pressure, focusing on how strategic behaviors such as skimming, scanning, and prioritizing questions influence comprehension and accuracy. The paper also examines cognitive factors, including working memory limitations and processing speed, which affect reading efficiency during timed assessments. Furthermore, the study discusses common challenges faced by test-takers and proposes pedagogical solutions for integrating time management strategies into language instruction. The findings contribute to the broader field of language assessment by emphasizing that successful test performance depends not only on linguistic competence but also on strategic testtaking skills.